Photocatalytic Hydrogen Evolution by a Synthetic [FeFe] Hydrogenase Mimic Encapsulated in a Porphyrin Cage. Issue 61 (9th October 2018) - Nurttila, Sandra S.; Becker, René; Hessels, Joeri; Woutersen, Sander; Reek, Joost N. H.
Abstract: The design of a biomimetic and fully base metal photocatalytic system for photocatalytic proton reduction in a homogeneous medium is described. A synthetic pyridylphosphole‐appended [FeFe] hydrogenase mimic was encapsulated inside a supramolecular zinc porphyrin‐based metal–organic cage structure Fe4 (Zn‐L)6 . The binding is driven by the selective pyridine–zinc porphyrin interaction and results in the catalyst being bound strongly inside the hydrophobic cavity of the cage. Excitation of the capsule‐forming porphyrin ligands with visible light while probing the IR spectrum confirmed that electron transfer takes place from the excited porphyrin cage to the catalyst residing inside the capsule. Light‐driven proton reduction was achieved by irradiation of an acidic solution of the caged catalyst with visible light. Abstract : Mimic in a cage : Synthetic pyridylphosphole‐appended [FeFe] hydrogenase mimic 1 was encapsulated in supramolecular zinc porphyrin‐based metal–organic cage Fe4 (Zn‐L)6 . Selective pyridine–zinc porphyrin interactions bind the catalyst strongly inside the hydrophobic cavity of the cage. Excitation of the porphyrin ligands with visible light results in electron transfer from the excited porphyrin cage to the encaged catalyst. Light‐driven proton reduction was achieved by visible‐light irradiation of an acidic solution of the caged catalyst (see figure).